PENGEMBANGAN APLIKASI PERMAINAN “PILAH SAMPAH” MENGGUNAKAN PEMODELAN FINITE STATE MACHINE - Admin APERTI (Aliansi Perguruan Tinggi Badan Usaha Milik Negara (APERTI BUMN), 2018)
This paper looks at how Finite State Machine (FSM) can be applied to design a game application namely “Pilah Sampah” as a business model diagram. “Pilah Sampah” aims to classify waste into organic and non-organic by using touch screen. In this game, scores will be added if an user can put the waste into the right place and vice versa. The type of FSM used in this paper is non- deterministic finite automaton (NFA) with epsilon (ϵ) transition or known as ϵ-NFA (Epsilon NFA). Basically, each transition, input and state of NFA shows the behaviour of the game. The importance of this research is to show that automata theory can be used to help a game developer to design a game. After doing blackbox test for “Pilah Sampah” game, it results that the game application can be developed by the ϵ-NFA modeling.